Improving Luminol Blood Detection in Forensics1. Issue 5 (22nd June 2016) - Stoica, Bogdan A.; Bunescu, Sabina; Neamtu, Andrei; Bulgaru‐Iliescu, Diana; Foia, Liliana; Botnariu, Eosefina Gina
Abstract: The aim of this study was to develop chemical improvements to the original Weber protocol, in order to increase the intensity and time length of light emission and to eliminate false‐positive reactions. The intensity and duration of light were measured on serial blood dilutions using a plate reader chemiluminometer. Blood stains of various concentrations were impregnated in pure cellulose, dried, and luminol solution was added with/without the potential enhancers. An in silico study was also conducted, aiming to demonstrate the enhancing mechanism of hemoglobin denaturation using 8 M urea. The luminol blood detection test revealed important improvements after urea pretreatment or in the presence of monochloro‐triazinyl‐β‐cyclodextrin. This approach also eliminated the false‐positive reaction from sodium hypochlorite. These improvements could provide a higher sensitivity under particular circumstances such as old or washed blood stains, leading to a better localization for further DNA typing and higher quality photographic analysis.